Studies on predatory mites inhabiting different stored products in north Kerala - Neeraj Martin (Malabar Christian College, University of Calicut, 2025)
India, a major producer and consumer of agricultural commodities, continues to facechallenges in managing stored product pests in warehouses and other storage environments.Despite growing awareness of chemical risks, fumigants remain widely used, raising concernsfor health, environment, and trade compliance. In this context, there is a growing need toexplore sustainable and biologically driven pest control alternatives. Predatory mites representa promising but underutilized resource in stored-product pest management. However, limitedstudies in tropical storage conditions, lack of rearing methodologies, and a narrow taxonomicfocus have hindered their practical application. The present study addresses these gaps througha holistic investigation into the diversity, biology, and applied potential of predatory mites fromstorage habitats in North Kerala, offering new insights and tools for future biocontrol strategies.This study provides a comprehensive assessment of the diversity, biology, and biocontrolpotential of predatory mites associated with stored products in North Kerala, India. A total of28 predatory mite species, representing 19 genera, 13 families, and 2 orders, were identifiedthrough surveys conducted across six districts and 61 storage facilities, including government-operated warehouses. Several taxa were newly recorded from India, including the descriptionof two new species viz., Acaropsella strioreticulata and Fessonia indica. These findingsexpand the known distribution of beneficial mites and emphasize their potential roles inintegrated pest management.The developmental biology of the dominant predatory mite species Cheyletusmalaccensis was investigated under varying temperature (25°C, 29°C, and 33°C) and relativehumidity (70%, 80%, and 90%) conditions. Results showed that 25°C with 70–80% RHfavoured higher fecundity, while 29°C with 80% RH promoted greater survival and fasterdevelopment. Feeding trials revealed clear predator-prey stage specificity, with adult femalesdemonstrating the highest predation efficiency against Suidasia nesbitti, particularly targetingits early life stages. To address methodological limitations in mite rearing, a custom 3D-printedPetri dish was designed and tested. This escape-proof, hygienic, and reusable system facilitatesobservational studies and has broad applicability across stored-product mite research.The study also established a novel mass-rearing protocol for C. malaccensis, achievinga 36.5-fold population increase in 30 days under controlled conditions. Importantly, thisresearch marks the first standardized method for mass-rearing C. malaccensis, a species notyet available commercially despite its global distribution and biocontrol potential.
Keywords: Predatory mites; Stored products; North Kerala; Acariformes; Cheyletidae